(untitled) (Acta Scientiarum. Technology, 2017)
The present study aimed to assess the possible beneficial effects of the integration between bioflocs and periphyton to the Nile tilapia´s water quality and growth performance. There were four treatments with five replicates each: (1) Control: green waters, (2) Periphyton: substrate-based system, (3) BFT: bioflocs technology for aquaculture, and (4) Biophyton: integration between bioflocs and periphyton. Fish (1.63 Â± 0.07 g) were reared for 10 weeks in twenty 250 L outdoor tanks. Two polyethylene boards were vertically set out in the Periphyton and Biophyton tanks as underwater substrates. The C: N ratios of water in the BFT and Biophyton tanks were adjusted to 15:1 with dry molasses applications. The concentrations of total ammonia nitrogen were higher in the Control and Periphyton tanks than in the BFT and Biophyton ones. On the other hand, the concentrations of reactive phosphorus were higher in the BFT and Biophyton tanks than in the Control and Periphyton ones. The fish final body weight, specific growth rate and fish yield have not differed between the tanks. The integration between bioflocs and periphyton has not brought clear benefits to tilapia culture on water quality and growth performance. Â Â